Effect of a viscoelastic interphase on the creep and stress/strain behavior of fiber-reinforced polymer matrix composites - Li, J.; Weng, G.J.
The influence of a viscoelastic interphase on the overall creep compliances and stress/strain relationships of fiber-reinforced polymer-matrix composites under a constant stress and a constant strain-rate loading are examined. The fibers are taken to be elastic but the matrix is also viscoelastic. Evaluation of the overall property is based upon the composite cylinder assemblage and the generalized self-consistent scheme. It is found that, except for the axial tensile behavior, which is fiber-dominated, the creep and stress/strain responses under transverse tension, transverse shear, axial shear, and plane-strain biaxial tension, are all significantly influenced by the interphase. A detailed examination of these effects in the light of the interphase property and volume concentration is carried out, and the results reveal that, when the interphase is viscoelastically softer than the matrix, its presence will cause a very pronounced influence on the creep strength and load-carrying capacity of the three-phase system.
Keywords: INTERPHASE; CREEP; STRESS-STRAIN BEHAVIOR; POLYMER COMPOSITES